2020
DOI: 10.1042/bsr20200570
|View full text |Cite
|
Sign up to set email alerts
|

Cellular localization of the FMRP in rat retina

Abstract: The fragile X mental retardation protein (FMRP) is a regulator of local translation through its mRNA targets in the neurons. Previous studies have demonstrated that FMRP may function in distinct ways during the development of different visual subcircuits. However, the localization of the FMRP in different types of retinal cells is unclear. In this work, the FMRP expression in rat retina was detected by Western blot and immunofluorescence double labeling. Results showed that the FMRP expression could be detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…These impairments may be due to the synaptic immaturity observed in post-mortem labeling in the visual cortex [31]. Retinal neurons share the same neuroectodermal embryonic origins with cortical neurons [32,33], and both neuron types express FMRP [34][35][36][37]. The retinal neural network shares similarities with other neural networks of the brain, in terms of connectivity [38,39], but the retina's accessibility allows for specific retinal signaling pathways to be probed and measured noninvasively with electroretinography (ERG).…”
Section: Introductionmentioning
confidence: 99%
“…These impairments may be due to the synaptic immaturity observed in post-mortem labeling in the visual cortex [31]. Retinal neurons share the same neuroectodermal embryonic origins with cortical neurons [32,33], and both neuron types express FMRP [34][35][36][37]. The retinal neural network shares similarities with other neural networks of the brain, in terms of connectivity [38,39], but the retina's accessibility allows for specific retinal signaling pathways to be probed and measured noninvasively with electroretinography (ERG).…”
Section: Introductionmentioning
confidence: 99%
“…Using double-labeling experiments, we further explored the co-expression pattern of SHANK3 and the different subtypes of ACs. GABAergic ACs, which account for a majority of ACs in the mammalian retina, are all large-field ACs labeled by GAD 65 (Halbedl et al, 2016;Zhang et al, 2020). As shown in Figure 4a', the somata of the GAD65-positive GABAergic ACs are located in the inner part of the INL and their processes are widely expressed in the IPL.…”
Section: Sh3 and Multiple Ankyrin Repeat Domains Protein 3 Is Widely ...mentioning
confidence: 98%
“…The retinas were prepared as previously described in detail (Zhang et al, 2020) with minor modifications. The mice were deeply anesthetized via 20% Urethane and transcardially perfused with saline followed by 4% paraformaldehyde (both ice-cold).…”
Section: Tissue Preparation For Immunocytochemistrymentioning
confidence: 99%
“…In addition, few studies focusing on Dark-Adapted (DA) conditions have also shown alteration in the b-wave amplitude (Constable et al, 2016). In parallel of these clinical works, preclinical data demonstrated that FMRP is expressed in all retinal layers (Rossignol et al, 2014;Guimaraes-Souza et al, 2016;Zhang et al, 2020) and that its total absence in young and adult Fmr1 KO mice (murine model of FXS) is associated to several protein deficits, neuronal immaturity, and thus to retinal functional alterations (Rossignol et al, 2014;Perche et al, 2018) as observed in human conditions (Perche et al, 2021). Moreover, retinal Fmrp content is dependent of light exposure, since studies showed higher levels of Fmrp RNA in retinas exposed to light when compared to DA retinas (Guimaraes-Souza et al, 2016).…”
Section: Short Communicationmentioning
confidence: 98%